PRESEPSI KESIAPAN GURU SMK DALAM MENERAPKAN MODEL PEMBELAJARAN BLENDED LEARNING - Bagus Putra; Hamid Abdillah; Haris Abizar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe teachers' understanding of the blended learning model and their perceptions in implementing blended learning. This study is a survey study with a quantitative approach with data obtained through interviews with several teachers, journals or scientific articles, and documents or files related to teachers' understanding of the blended learning model. While the data analysis technique used is quantitative descriptive to describe and explain the overall data that will be concluded at the end of the study. This study concluded that some teachers do not understand the blended learning model, which indirectly means some teachers are still not ready to implement the blended learning model. The results of this study are expected to be used as a benchmark in improving teacher quality in learning and as a reference for further research on blended learning.